On a Certain Method for Parameter Estimation of a Mechanical System with Sensitivity Model Application - Wicher, J. (Engineering Transactions, 1982)
The parameter estimation problem of a linear mechanical system with n degrees-of-freedom has been considered. The lumped masses of this system are connected by any combination of stiffness and viscous damping elements (called the rheological models). The sensitivity model of the system is used in a presented algorithm.